ANALISIS KAPASITAS PENAMPANG BANJIR KANAL BARAT KOTA SEMARANG UNTUK PERENCANAAN PENGENDALIAN BANJIR - Reza Juan Prakasa; Ridho Anggoro; Abdul Kadir; Al Falah (Jurnal Karya Teknik Sipil, 2013)
Overflow  in the West Floodway  is a natural event caused by inadequate river capacity to flow the existing discharge.Based on the analysis of hydrological West Floodway with the help of software HEC-HMS (Hydrologic Engineering Center-Hydrologic Modeling System) obtained discharge plan (Q50) of  951.9 m3/s.  The hydraulics analysis  was carried out by the help of software HEC-RAS (Hydrologic Engineering Center-River Analysis System)and the result is an overflow along the 8 km (WF 0-WF 97) in the West Floodway Region. To overcome these  problems, it is necessary to be taken a solution,  that is increasing river capacity. Based on existing field conditions  (limited space) then the plan is  using  2 type of river  profiles, there are at the downstream  river is used for single and double crosssection on the upstream, both is planning  using manning formula.